Sifat Kimia Tanah pada Budidaya Talas Beneng (Xanthosoma undipes K.Koch) di Berbagai Ketinggian - Aghnia Sholihat; Nuniek Hermita; Julio Eiffelt Rossafelt Rumbiak; Dewi Firnia (Jurnal Ilmiah Membangun Desa dan Pertanian, 2024)
Soil is important in agriculture because of its chemical properties, which can affect plant growth. Understanding soil chemical characteristics at various elevations is expected to help identify the optimal elevation for Beneng taro cultivation. This study aims to identify the chemical properties of soil used for Beneng taro cultivation at different elevations to determine optimal conditions for plant productivity. The research uses a descriptive quantitative method conducted in three villages at varying elevations: Talaga Warna Village in Pabuaran District (343 meters above sea level), Juhut Village in Karangtanjung District (±615 meters above sea level), and Kaduengang Village in Cadasari District (±761 meters above sea level). The study was carried out from August to October 2024. Sampling was conducted using a composite method with a diagonal sampling technique. The soil chemical parameters analyzed include pH (measured by penetration method), C-Organic (Walkley and Black method), Total Nitrogen (Kjeldahl method), Total Phosphorus and Total Potassium (25% HCl extraction method), and Cation Exchange Capacity (CEC) using the NH4OAc method at pH 7. Soil chemical analysis was performed at the Agroecotechnology Soil Laboratory, Sultan Ageng Tirtayasa University, and Laboratory IPB. Research findings will be presented in tables and maps using ArcGIS software. Results indicate that soil chemical properties for Beneng taro cultivation vary across elevations. The soil at different elevations is generally acidic, with very low levels of Total Nitrogen, Total Phosphorus, and Total Potassium, as well as low C-Organic content, while soil CEC is categorized as moderate. This study provides a scientific basis for enhancing Beneng taro production by considering optimal elevation and suitable soil conditions.